2019
DOI: 10.1073/pnas.1908353116
|View full text |Cite
|
Sign up to set email alerts
|

KRAS G13D sensitivity to neurofibromin-mediated GTP hydrolysis

Abstract: KRAS mutations occur in ∼35% of colorectal cancers and promote tumor growth by constitutively activating the mitogen-activated protein kinase (MAPK) pathway. KRAS mutations at codons 12, 13, or 61 are thought to prevent GAP protein-stimulated GTP hydrolysis and render KRAS-mutated colorectal cancers unresponsive to epidermal growth factor receptor (EGFR) inhibitors. We report here that KRAS G13-mutated cancer cells are frequently comutated with NF1 GAP but NF1 is rarely mutated in cancers with KRAS codon 12 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
92
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 40 publications
14
92
1
Order By: Relevance
“…More recently, the 3D structure of a complex between K-Ras (GMPPNP-bound) and a fragment of the neurofibromin-GRD (GAP255: residues 1209 to 1463), corresponding to the minimum catalytic region (the C-and N-terminal regions forming the extra domain were excluded), was resolved [47] ( Figure 5), confirming the insights given by the model. This was the first structure of a Rasneurofibromin GRD complex and of a Ras-Ras GAP complex in the ground-state conformation.…”
Section: The Gap-related Domain (Grd)supporting
confidence: 61%
“…More recently, the 3D structure of a complex between K-Ras (GMPPNP-bound) and a fragment of the neurofibromin-GRD (GAP255: residues 1209 to 1463), corresponding to the minimum catalytic region (the C-and N-terminal regions forming the extra domain were excluded), was resolved [47] ( Figure 5), confirming the insights given by the model. This was the first structure of a Rasneurofibromin GRD complex and of a Ras-Ras GAP complex in the ground-state conformation.…”
Section: The Gap-related Domain (Grd)supporting
confidence: 61%
“…RAS proteins have two mutational hotspots, 12-13 and 61. Most mutations changing G12 or G13, likely to intercept GAP's Arg finger loop accession to the RAS GTPase site and prevent it from promoting hydrolysis [246][247][248]. As a consequence, G12 and G13 mutants trap RAS in a constitutively active state.…”
Section: Ras Mutationsmentioning
confidence: 99%
“…The GRD has a central portion called the minimal catalytic domain (GAPc) and an extra domain (GAPex) formed by residues that flank the GAPc. Although the apo structure of the NF1(GRD) was solved more than 2 decades ago ( Scheffzek et al, 1998 ), our recent structural work on GMPPNP-bound KRAS in complex with the GAPc of NF1(GRD) provided structural insights into NF1-mediated GTPase activity ( Rabara et al, 2019 ). In that study, we showed that, unlike G12 and Q61 mutants, G13 mutants of KRAS are frequently co-mutated with NF1 and that NF1 hydrolyzes GTP directly in complex with KRAS-G13D.…”
Section: Introductionmentioning
confidence: 99%